The Performance Of Employees Of Banks With Work Motivation as Moderator - YAMAWATI, Ni Kd. Sioaji; DEWI, I Gusti Ayu Ratih Permata (International Journal of Environmental, Sustainability, and Social Science, 2021)
This study aims to influence the effectiveness of accounting information systems and work motivation on employee performance. Furthermore, work motivation is a moderator between the effectiveness of accounting information systems and employee performance. This research was conducted at the Rural Bank (BPR) in Gianyar Regency. Retrieval of samples with Purposive Sampling technique. Technical analysis of the data used is using the approach Partial Least Square (PLS). Results of the study show that the effectiveness of the accounting information system and motivation to work affect the performance of employees. Furthermore, work motivation can moderate the effect of the effectiveness of accounting information systems on employee performance.